Food analysis by HPLC - Nollet, Leo M. L., 1948-; Toldra, Fidel (CRC Press, 2013)
For food scientists, high-performance liquid chromatography (HPLC) is a powerful tool for product composition testing and assuring product quality. Since the last edition of this volume was published, great strides have been made in HPLC analysis techniques-with particular attention given to miniaturization, automatization, and green chemistry.